Kedudukan Hukum Notaris Merangkap Jabatan Sebagai Arbiter Ditinjau Dari Undang-Undang Jabatan Notaris - Ister Angelia (Jurnal Ilmu Kenotariatan, 2024)
As the business world develops and the world of trade develops, it cannot be denied that the possibility of disputes will arise between the parties. Then another way is known that provides the possibility for the disputing parties to bring and resolve the case that arises outside the court if they wish, namely through arbitration, where the settlement of the case is carried out by the Arbiter, by making a written agreement. This agreement is often made by a Notary, so that not a few Notaries who also serve as arbitrators. However, there is no regulation in the Notary Law that explicitly regulates Notaries who also serve as Arbitrators. The research method used is Normative Jurisprudence, the approach in this study uses a statutory approach and a conceptual approach. A Notary is a public official who is authorized to make authentic deeds and other authorities as referred to in the Notary Law. A Notary is required to act professionally in carrying out his/her position by heeding the prohibitions contained in the provisions governing the position of the Notary. Notaries who will hold concurrent positions as arbitrators are not prohibited, because basically both positions have similarities, among others, both function to avoid further disputes between the parties, only the notary concerned needs to wisely regulate the mechanism of his work and the time that will be used due to his dual position. Notaries also need to pay attention to which legal rules bind him when carrying out one of his dual positions. So that a balance can be achieved in carrying out the dual position. KEYWORDS: Notary, Arbitrator, Arbitration, Dual Position